Indigenous water rights in law and regulation : lessons from comparative experience / Elizabeth Jane Macpherson. - Macpherson, Elizabeth Jane, 1981- (Cambridge studies in law and society., 2019)
Indigenous Water Rights in Law and Regulation responds to an unresolved question in legal scholarship: how are (or how might be) indigenous peoples' rights included in contemporary regulatory regimes for water. This book considers that question in the context of two key trajectories of comparative water law and policy. First, the tendency to 'commoditise' the natural environment and use private property rights and market mechanisms in water regulation. Second, the tendency of domestic and international courts and legislatures to devise new legal mechanisms for the management and governance of water resources, in particular 'legal person' models. This book adopts a comparative research method to explore opportunities for accommodating indigenous peoples' rights in contemporary water regulation, with country studies in Australia, Aotearoa New Zealand, Chile and Colombia, providing much needed attention to the role of rights and regulation in determining indigenous access to, and involvement with, water in comparative law.